Process of Transmitting the Babalu Dance at Putra Budaya Studio Batang Regency - Kusumaningtyas, Chandra Dewi; Cahyono, Agus; Lestari, Wahyu (Jurnal Seni Tari, 2025)
Babalu Dance is a traditional art form from Batang Regency that carries significant historical meaning related to local resistance against colonial powers. As globalization advances, the younger generation's interest in Babalu Dance has decreased. This study describes the inheritance process of Babalu Dance conducted at Sanggar Putra Budaya. A qualitative method with an ethnographic approach was applied. Data were collected through observation, interviews, literature review, and documentation. The research shows that Babalu Dance consists of various movements, themes, make-up, costumes, musical accompaniment, properties, floor patterns, and stage formations reflecting resistance values. The inheritance process follows a diagonal system, using non-formal education that includes regular training, cultural value dissemination, and active youth participation. Sanggar Putra Budaya serves as a crucial institution in maintaining Babalu Dance preservation amidst modernization challenges.